Local food system and household responses to external shocks: The case of sustainable coffee farmers and their cooperatives in Western Honduras during COVID-19 - Rodriguez-Camayo, Fernando; Lundy, Mark; Borgemeister, Christian; Ramirez-Villegas, Julian; Beuchelt, Tina (Frontiers Media, 2024)
Introduction: The COVID-19 pandemic lockdowns (people confined to home, with movement restrictions) presented an external shock to livelihoods and food systems worldwide, most severely affecting vulnerable households in low-income countries. While evidence is available regarding how COVID-19 generally affected low-income countries, the specific dynamics of local food-system responses and sustainably-certified coffee farm households has not been examined, despite them being usually deemed to be more resilient to shocks. This research examines how local food systems in Honduras changed during lockdowns, how certified coffee households coped with the shock, especially food insecurity, and the potential role of coffee cooperatives in increasing households’ resilience under future shocks and stressors.